Stock Returns and the Weekend Effect: the Malaysian Experience - Md. Nasir, Annuar; Mohamad, Shamsher; Abdul Hamid, Mohamad Ali (1988)
Market behaviour of stock returns and the weekend effect were investigated. Our study confirms the presence of the day of the week effect or Monday effect in the Malaysian Stock Market. In particular, over the 1975-1985 periods, the lowest mean return occurred on Tuesday and both Monday and Tuesday returns were negative.